Critical need for pharmacologic treatment options in NAFLD: A pediatric perspective - Chance S. Friesen; Sherwin S. Chan; Jonathan B. Wagner; Chelsea Hosey‐Cojocari; Iván L. Csanaky; Valentina Shakhnovich (Wiley, 2021)
Abstract Nonalcoholic fatty liver disease (NAFLD) affects up to 70% of children with obesity and has become the number one etiology for liver transplant in the United States. Early, effective intervention is critical to prevent disease progression into adulthood. Yet, it is seldom achieved through lifestyle modification alone. Thus, children must be included in NAFLD pharmacology trials, which, to date, continue to focus primarily on adult populations. This commentary serves as a call to action.